Septic Arthritis in an Immunocompetent Adult: A Case Report and Review of Literature - Rakan E. Dodin MD; Hallie Thompson MD; Michael H. Storandt MD; Leonid Vilenski MD; Dubert M. Guerrero MD (SAGE Publishing, 2023)
Septic arthritis is a medical emergency that requires prompt diagnosis to prevent long-term intra-articular complications. Prevotella bivia is an anaerobic gram-negative rod which has been infrequently reported to cause septic arthritis. We present a 49-year-old female that presented with spontaneous left knee pain and swelling without history of insult to the knee. She was initially misdiagnosed with patellar tendinitis and gout but later underwent joint aspiration due to worsening symptoms, which demonstrated 60 800/µL nucleated cells with a polymorphonuclear burden consistent with septic arthritis. Arthroscopy with irrigation and drainage was subsequently performed, and the patient was started on empiric antibiotics while awaiting cultures. Cultures grew Prevotella bivia , and antibiotics were deescalated to ertapenem alone followed by oral metronidazole. Prevotella species as a source of septic arthritis is rare, and its occurrence in a patient without known insult to the knee is even more uncommon. It is essential that it is recognized to treat appropriately and prevent long-term loss of function in the joint.